2019
DOI: 10.3168/jds.2018-16022
|View full text |Cite
|
Sign up to set email alerts
|

Bedding and bedding management practices are associated with mesophilic and thermophilic spore levels in bulk tank raw milk

Abstract: Mesophilic and thermophilic spore-forming bacteria represent a challenge to the dairy industry, as these bacteria are capable of surviving adverse conditions associated with processing and sanitation and eventually spoil dairy products. The dairy farm environment, including soil, manure, silage, and bedding, has been implicated as a source for spores in raw milk. High levels of spores have previously been isolated from bedding, and different bedding materials have been associated with spore levels in bulk tank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
2
16
1
Order By: Relevance
“…Miller et al (2015b) also found that the use of straw bedding was associated with lower incidence of thermophilic spore counts in bulk tank raw milk. Similarly, a recent study of spore levels in new (unused) and used bedding and bulk tank raw milk across 18 states found that mesophilic and thermophilic spore levels in new bedding directly and indirectly affected the mesophilic and thermophilic spore levels in bulk tank raw milk (Murphy et al, 2019). Further, Murphy et al (2019) reported that bedding management practices, such as how often bedding was topped up or changed was significantly associated with spore levels in bulk tank raw milk, further supporting our findings.…”
Section: Both Environmental and Cow Hygiene Factors Affect Spore Transupporting
confidence: 87%
See 2 more Smart Citations
“…Miller et al (2015b) also found that the use of straw bedding was associated with lower incidence of thermophilic spore counts in bulk tank raw milk. Similarly, a recent study of spore levels in new (unused) and used bedding and bulk tank raw milk across 18 states found that mesophilic and thermophilic spore levels in new bedding directly and indirectly affected the mesophilic and thermophilic spore levels in bulk tank raw milk (Murphy et al, 2019). Further, Murphy et al (2019) reported that bedding management practices, such as how often bedding was topped up or changed was significantly associated with spore levels in bulk tank raw milk, further supporting our findings.…”
Section: Both Environmental and Cow Hygiene Factors Affect Spore Transupporting
confidence: 87%
“…Similarly, a recent study of spore levels in new (unused) and used bedding and bulk tank raw milk across 18 states found that mesophilic and thermophilic spore levels in new bedding directly and indirectly affected the mesophilic and thermophilic spore levels in bulk tank raw milk (Murphy et al, 2019). Further, Murphy et al (2019) reported that bedding management practices, such as how often bedding was topped up or changed was significantly associated with spore levels in bulk tank raw milk, further supporting our findings. Given that dairy cows spend 12 to 14 h each day lying down (Gomez and Cook, 2010), with direct contact between teat and udder surfaces and bedding, it is unsurprising that spores in bedding and bedding management are important variables in the transmission of spores into bulk tank raw milk.…”
Section: Both Environmental and Cow Hygiene Factors Affect Spore Transupporting
confidence: 87%
See 1 more Smart Citation
“…The level of this contamination is closely related to hygienic conditions of milking, state cleanliness of animal, material used, environment, knowledge and to application the good practices of rules hygiene by the actors (Maiwore et al, 2018;Millogo et al, 2018;Cissé et al, 2019). Some microorganisms pass transiently into their food producing toxins or spores, which after ingestion are very fatal for consumers (Murphy et al, 2019;Xiong et al, 2019). The presence of certain contaminants does not render this food completely unfit for human consumption, but depends the limited dose.…”
Section: Discussionmentioning
confidence: 99%
“…The main organisms involved in PPC associated with finished product spoilage are heat-labile gram-negative bacteria, including Pseudomonas and the Enterobacteriaceae, which can be introduced into finished products from a variety of potential sources, including contaminated equipment, contaminated aerosols, and cross-contamination from employees (Sunga et al, 1970;Schröder, 1984;Eneroth et al, 2000b). Although thermoresistant gram-positive bacteria, including sporeformers, could also be introduced after pasteurization (Eneroth et al, 2001), endospores formed by these bacteria are often present in the raw milk supply (Murphy et al, 2019) and endospore numbers are typically not reduced by HTST. While psychrotolerant sporeformers and, to a much lesser extent, non-spore-forming gram-positive bacteria cause fluid milk spoilage, they are thus excluded from our PPC definition used in this publication.…”
Section: Introductionmentioning
confidence: 99%